Construction of Ultrasonic Fruit Fly Repellent Device in Orange Orchard. Issue 1 (1st January 2023) - Rahayu, S U; Nasruddin; Susilawati; Sianturi, H A; Faturrahman; Manurung, J G
Abstract: Ultrasonic waves are stated to be able to repel several types of pests. This study aimed to design a device to repel fruit fly in orange orchard using ultrasonic waves with a frequency range of 20-80 KHz. The device employed a microcontroller and real time clock (RTC) to control the ultrasonic wave transmitter automatically, in which the electrical energy is obtained from solar panel. The objective of using the solar panels is to directly powered device without installing the cable to the main power source (PLN) because the device should be placed in the middle of the orchard, which is located far from the main power source. Based on the design analysis, the solar panel should be placed facing the southern part of the orchard with the angle of around 5ºC since the orchard in the Karo regency, Sumatera Utara, Indonesia. The current was measured for each frequency, and based on that measurement the electrical power was calculated to be 142.56 Watt, so by using the battery of 1200 Watt, the device could work properly for 8 hours even without full sunlight. The resulted frequency was measured using oscillator; the results show that the average accuracy is 0.24%, which shows that the ultrasonic wave transmitters generate the ultrasonic wave accurately. Based on these results, it can be concluded that the ultrasonic fruit fly repellent device designed in this study is successfully constructed and works properly to generate the ultrasonic wave with the range frequency satisfied the condition to repel the fruit fly.